Comparación del método microbiológico con cromatografía liquida de alta resolución (hplc) en la detección de residuos de quinolonas y fluoroquinolonas en musculo de peces salmonideos - San Martín, Betty; Cañón, Hernán; Quiróz, Alejandra; Hernández, Patricia (Avances en Ciencias Veterinarias, 2000)
A comparison between a microbiological assay and HPLC for the detection of enrofloxacin, oxolinic acid and flumequine residues in salmon muscle was studied. The limit of detection of the microbiological assay for enrofloxacin, oxolinic acid and flumequine was 10, 40 and 300 ppb, respectively and HPLC was 5 ppb for all the drugs studied. These sensitivities were lower than those described previously. The main difference for the microbiological assay and HPLC could relate to the indicator organism concentration and the aliquot injected, respectively. The results suggest that the microbiological assay could be used as screening with a confirmatory method by HPLC within a residue monitoring program for these drugs.